Supplementary Education in Turkey: Recent Developments and Future Prospects - Aysit Tansel (Institute for the Study of Labor (IZA), 2013)
Purpose: This paper aims to provide the recent developments on the supplementary education system in Turkey. The national examinations for advancing to higher levels of schooling are believed to fuel the demand for Supplementary Education Centers (SEC). Further, we aim to understand the distribution of the SECs and of the secondary schools across the provinces of Turkey in order to evaluate the spacial equity considerations. Design/Methodology/Approach: The evolution of the SECs and of the secondary schools over time are described and compared. The provincial distribution of the SECs, secondary schools and the high school age population are compared. The characteristics of these distributions are evaluated to inform the about spatial equity issues. The distribution of high school age population that attend secondary schools and the distribution of the secondary school students that attend SECs across the provinces are compared. Findings: The evidence points out to significant provincial variations in various characteristics of SECs and the secondary schools. The distribution of the SECs is more unequal than that of the secondary schools. The provinces located mostly in the east and south east of the country have lower quality SECs and secondary schools. Further, the SEC participation among the secondary school students and the secondary school participation among the relevant age group are lower in some of the provinces indicating major disadvantages. Originality/Value: The review of the most recent developments about the SECs, examination and comparison of provincial distributions of the SECs and of the secondary schools are novelties in this paper.
Keywords: I20; I21; I22; 330; supplementary education; demand for education; Turkey